Astronomy today - Chaisson, Eric (Prentice Hall, 1999)
This number one, best-selling astronomy text reflects the most current findings in astronomy using a clear, accurate exposition, market-leading art program, and the most innovative, integrated media program available. A free CD is included with each copy of the text with a multimedia version of the text and links directly to the widely praised Chaisson/McMillan companion web site at http://www.prenhall.com/chaisson. The CD contains approximately 35 updates on events and discoveries that have occurred since the print-based book was published.